Klinikopatologik dan Profil Imunohistokimia Primary Mediastinal Large B-cell Lymphoma dan Limfoma Hodgkin Nodular Sclerosis di Regio Mediastinum - Dameria, Flora; Francisca Ham, Maria; Stephanie Harahap, Agnes (Majalah Patologi Indonesia, 2023)
Background Primary mediastinal large B-cell lymphoma (PMBCL) and Hodgkin nodular sclerosis (LHNS) lymphoma was the most common lymphomas involved the mediastinum. These two lymphomas had similar histopathological features. The purpose of this study was to analyzed clinical data, histopathological characteristics, and immunohistochemistry (IHC) profiles on PMBCL and LHNS. Methods This is a retrospective study. Data was collected from archive of Anatomical Pathology Department, Faculty of Medicine, Universitas Indonesia/Cipto Mangunkusumo Hospital in 2014-2020. The data collected included clinical data, hematoxylin-eosin (HE) and IHC slides and were reassessed by the researcher and supervisor. The histopathological characteristics data was analyzed statistically using statistical package for the social sciences version 25.0 with Chi-Square test. Results PMBCL and LHNS have similar histopathological features, included the characteristics of tumor cells and infiltration of many fibrosis and inflammatory cells, but difference in architecture, tumor cell types, clear cytoplasmic tumor cells, inflammatory cell and fibrosis types, with p value <0.001. The characterized differences of PMBCL showed diffuse architecture, some cells with RS-like cell structure, clear/pale cytoplasm, lymphocyte cell infiltration, and compartmental fibrosis. Whilst, LHNS showed nodular architecture, Reed Sternberg cells, mixed inflammatory cell infiltration, and band-like fibrosis. PMBCL showed CD20, PAX5, MUM1 strongly positive, CD30 weakly positive, and CD15 negative, while LHNS showed negative CD20, CD30 and MUM1 strongly positive, PAX5 weakly positive, and CD15 positive.